فعالية طريقة الاستجابة الجسدية الكلية لترقية مهارة الكلام للفصل العاشر في المدرسة دار الصالحين نهضةالوطن الثانوية الإسلامية دارماجي - Imron Husen; Suaidi, Suaidi; Hudatullah, Ruwaida (Lughatu Ad-dhat, 2024)
The Total Physical Response method is a language teaching method that is built on the basis of coordination between speech and action. Speaking skills are the ability to express the sounds of articulation of words to express thoughts in the form of ideas. After making observations in the field, the researcher found several problems in learning Arabic, such as students' lack of enthusiasm during the learning process, and so on. So that a more interesting method is needed in learning Arabic such as the total physical response method so that students are able to get used to speech and gestures when memorizing or when holding simple conversations. The aims of this study were: (1) To find out the application of the Total Physical Response method in improving Arabic speaking skills for class X MA Darussholihin NW Darmaji, (2) To find out the effectiveness of the Total Physical Response method in improving Arabic speaking skills for class X MA Darussholihin NW Darmaji. The results of this study are: 1) The application of the Total Physical Response method in this study used two methods, namely showing pictures for the vocabulary of family members and singing for the vocabulary of body members, and the results made the class conditions more conducive. (2) The effectiveness of the Total Physical Response method is known from the results of the T-Test test which shows the results that the significance value obtained from the independent T-test using the SPSS 25 output is 0.005, meaning that it is smaller than the a value of 0.05, which is in accordance with the rule testing Ho, it can be stated that Ho is rejected and Ha is accepted. And this is also proven by looking the result of the average score obtained, where the average score in the pretest in the experimental class was 58 and in the posttest the average score was 62,19 as well as in the control class the average score in the pretest was 53,11 and in the posttest was 55,59. With the meaning that the use of the total Physical Response method is effective in improving the Arabic speaking skills of class X MA Darussholihin NW Darmaji. Keywords: Total Physical Response Method, Speaking Skills